A darkened reading : a reception history of the book of Isaiah in a divided church - Knetsch, Robert L. (Eugene, Oregon : Pickwick Publications, 2014)
"The church in the West has subsisted for five hundred years in a state of ever-increasing multiple identities, many of which claim to be the best representation of the church established by Christ. Often attending novel models of the church are new scriptural interpretive methods that support theological claims. Rarely, however, has an exploration been undertaken to test the impact of the ecclesiological division on the reading of the Bible. A darkened reading explores the specific case of the nineteenth-century Church of England and competing interpretations of the book of the prophet Isaiah-- a book of great importance in theological history-- as a kind of parable of the existential anguish the church has experienced as a consequence of being torn apart."-- back cover.
Includes bibliographical references and index.
Print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Church of England -- History -- 19th century; England -- Church history -- 19th century; RELIGION / Biblical Studies / Prophets; Electronic books